Modernism and Masculinity / [electronic resource] - Lusty, Natalya; Murphet, Julian (Cambridge : Cambridge University Press, 2014)
Modernism and Masculinity investigates the varied dimensions and manifestations of masculinity in the modernist period. Thirteen essays from leading scholars reframe critical trends in modernist studies by examining distinctive features of modernist literary and cultural work through the lens of masculinity and male privilege. The volume attends to masculinity as an unstable horizon of gendered ideologies, subjectivities and representational practices, allowing for fresh interdisciplinary treatments of celebrated and lesser-known authors, artists and theorists such as D. H. Lawrence, Ezra Pound, Henry Roth, Theodor Adorno and Paul Robeson as well as modernist avant-garde movements such as vorticism, surrealism and futurism. As diverse as the masculinities that were played out across the early twentieth century, the approaches and arguments featured in this collection will appeal especially to scholars and students of modernist literature and culture, gender studies and English literature more broadly.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Modernism (Literature); Masculinity in literature; Modernism (Art)